The Professional Development Challenges Faced By The English Novice Teachers In Post-Pandemic - Naurah Nazhifah (Eduvest - Journal of Universal Studies, 2024)
This qualitative study investigates novice English teachers' perceptions of their professional development and the challenges that they experience in their teaching careers. A questionnaire and semi-structured interviews were used to obtain data from two novice English teachers. Purposive sampling was utilized to identify participants who may give beneficial insights into the subject matter of the study. According to the findings of the study, both teachers displayed an extensive understanding of the pedagogical competencies essential to effective teaching, demonstrating the necessity of continuous advancement in academic skills, teaching techniques, and subject competence. They recognized professional development as a combination of formal experiences, such as workshops and mentorship, as well as informal experiences related to their academic discipline. Furthermore, the novice teachers highlighted the significance of personal and social competencies in their professional journey, including individual skills, positive personality traits, and fostering strong relationships with students and their families. In regard to professional development approaches, one teacher participated actively in the school's professional development program and attended seminars, whilst the other is currently studying for a master's degree to improve teaching quality and strengthen knowledge. The two approaches emphasized the need for continuous development and learning in the professional experiences of novice teachers. The study additionally highlighted challenges that novice teachers encounter, such as difficulty responding to curricular shifts, limited resources, and concern about employment rights. These findings shed light on the experiences faced by novice English teachers and offer suggestions for strengthening professional development programs and educational support systems.